Stemphol galactoside, a new stemphol derivative isolated from the tropical endophytic fungus Gaeumannomyces amomi - Jumpathong J. (2014)
A new stemphol derivative, stemphol 1-O-β-D-galactopyranoside (1b), together with three known metabolites, stemphol (1a), indole-3-carboxylic acid, and kojic acid, has been isolated from the ethyl acetate extract of cultures of Gaeumannomyces amomi BCC4066, an endophytic fungus found on healthy parts of ginger (Alpinia malaccensis; Thai name Kha-pa). The structure of 1b was established via spectroscopic methods, including 2D NMR measurements and GC/MS experiments.